2006
DOI: 10.2460/javma.229.9.1451
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival and risk factors associated with biliary surgery in dogs: 34 cases (1994–2004)

Abstract: Long-term prognosis was guarded after biliary surgery in dogs. However, dogs that survived the early postoperative period had good long-term prognosis. Dogs with pancreatitis had poor prognosis. Overall, the prognosis was worse for dogs that underwent a biliary diversion, compared with dogs that did not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
126
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(132 citation statements)
references
References 19 publications
6
126
0
Order By: Relevance
“…Previous studies have shown PTT times, serum concentrations of albumin, globulin, and bilirubin, percentage of band neutrophils, and total lymphocyte counts to also be risk factors for death 10,12,13 In the same studies, reported preoperative risk factors for death in dogs undergoing biliary surgery include age, preanesthetic heart rate, blood urea nitrogen, serum creatinine, GGT, phosphorus, and bilirubin values. 10,12 The risk of death in our dogs increased 0.3 times (30%) for each increment in lactate concentration elevation in the postoperative period. Serum lactate concentrations have been previously investigated in dogs as a significant negative prognostic indicator in disease processes such as gastric dilatation and volvulus, and babesiosis.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Previous studies have shown PTT times, serum concentrations of albumin, globulin, and bilirubin, percentage of band neutrophils, and total lymphocyte counts to also be risk factors for death 10,12,13 In the same studies, reported preoperative risk factors for death in dogs undergoing biliary surgery include age, preanesthetic heart rate, blood urea nitrogen, serum creatinine, GGT, phosphorus, and bilirubin values. 10,12 The risk of death in our dogs increased 0.3 times (30%) for each increment in lactate concentration elevation in the postoperative period. Serum lactate concentrations have been previously investigated in dogs as a significant negative prognostic indicator in disease processes such as gastric dilatation and volvulus, and babesiosis.…”
Section: Discussionmentioning
confidence: 88%
“…7,9 Although the reported perioperative mortality ranges from 21.7% to 40%, 1,2,8 the prognosis for a dog with GM undergoing cholecystectomy is generally favorable if the dog survives the immediate postoperative period. 1,2,[10][11][12] Long-term outcome for dogs surviving surgery and the immediate postoperative period is good with 1 study reporting both 1-and 2-year survival rates of 22 of 34 (66%). 10 Our objectives were to report the clinical and intraoperative findings in dogs with GM undergoing cholecystectomy and to determine prognostic factors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The main risk factors for the development of gallstones in humans are age, heredity, parity and obesity; occurring mainly in people over 55 years, and a greater incidence among women [5][6][7][8] . There are several conditions that, in humans and animals, can cause obstruction in the biliary tree, occurring cholestasis [9][10][11][12][13] . However, in recent years, there was an increase in the diagnosis of asymptomatic lithiasis due to upgrading diagnostic methods routinely performed in patients [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…Those findings will be used in successive experiments with prolonged time of postoperative histopathological evaluation to determine the character of bile-induced changes in the jejunal mucosa (Amsellem et al 2006). In clinical patients (cats and dogs), cholecystoenterostomy is usually the only form of treatment during surgical interventions (Tangner 1984).…”
Section: Discussionmentioning
confidence: 99%